2017
DOI: 10.1021/acs.jafc.7b02003
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Dietary Oxidized Tyrosine and Dityrosine Administration in Mice with Nutrimetabolomic Strategies

Abstract: This study aims to investigate the health effects of long-term dietary oxidized tyrosine (O-Tyr) and its main product (dityrosine) administration on mice metabolism. Mice received daily intragastric administration of either O-Tyr (320 μg/kg body weight), dityrosine (Dityr, 320 μg/kg body weight), or saline for consecutive 6 weeks. Urine and plasma samples were analyzed by NMR-based metabolomics strategies. Body weight, clinical chemistry, oxidative damage indexes, and histopathological data were obtained as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 83 publications
2
56
0
Order By: Relevance
“…Particular protein oxidation products, such as protein carbonyls, the α‐amino adipic acid, tyrosine, tryptophan, and phenylalanine oxidation products, among others, initially exposed to the intestinal mucosa, are absorbed and hence, accumulate in the epithelium and may be distributed to distant internal organs through the bloodstream (Ding, Cheng et al., , Ding, Li et al., ; Wang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Particular protein oxidation products, such as protein carbonyls, the α‐amino adipic acid, tyrosine, tryptophan, and phenylalanine oxidation products, among others, initially exposed to the intestinal mucosa, are absorbed and hence, accumulate in the epithelium and may be distributed to distant internal organs through the bloodstream (Ding, Cheng et al., , Ding, Li et al., ; Wang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
“…The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues. This is the case of protein carbonyls for the intestinal epithelium (Keshavarzian et al., ), the α‐amino adipic acid for pancreas (Wang et al., ), and oxidized tyrosines for pancreas, kidney and liver (Ding, Cheng et al., ; Ding, Li et al., ; Ding, Tang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). Finally, it is worth noting that the elevation of protein oxidation markers in blood and tissues may not only be caused by the intake of such species.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A relatively new study identified certain tyrosine and tryptophan oxidation products as discriminating metabolites during digestion of red meat versus white meat, suggesting that these species may play a still unclear role in the pathogenesis of these disorders. A recent review and several original articles emphasized the role of assorted protein oxidation products, including protein carbonyls, oxidized tryptophan, and dityrosines, on various health disorders …”
Section: Introductionmentioning
confidence: 99%